Molecular Iodine-Mediated Synthesis of 2-Azaanthraquinones from [3.3.3]Propellanes via a Metal-Free Rearrangement - Alizadeh, Abdolali; Bagherinejad, Akram; Khanpour, Mojtaba (Synthesis, 2021)
A novel iodine-mediated rearrangement of heterocyclic [3.3.3]propellanes under green conditions is described. This metal-free transformation for the straightforward synthesis of substituted 2-azaanthraquinones proceeds via ring opening/dissociation of C–O and C–N bonds/intramolecular C(sp3)–C(sp3) bond formation/ring expansion/aza-ring closure/1,3-N to N alkyl migration. High atom-efficiency, synthetically useful yields, easily accessible starting materials, and mild reaction conditions are advantages of this process.
Keywords: heterocyclic [3.3.3]propellanes; metal-free transformation; redox-mediated rearrangement; amidine rearrangement; 2-azaanthraquinones; one-pot four-component reaction